DOF (Departamento de Operações de Fronteira): um estudo de integração de polícias civil e militar - Barbosa, André Martins (2009)
This doctoral thesis aims to verify the possibility of an integrated work between civil and military police forces under a joint command and within the same police unit. It is based on the assumption that the tussle involving both law enforcement agencies has been gradually built up in the inner structures of the Brazilian s security state, culminating in a secession caused by conflicts between the administrative and the judicial police. This study regards the frontier area between Brazil, Paraguay and Bolívia, in which the Borderline Operations Department (BOD) runs and is located since its creation in 1987. The methodological approach chosen in this thesis favored the assemblage of regionally broadcasted interviews, speeches and writings of the authorities and personalities (local and other states), data from the DOF itself, the State of MS, Civil and Military Police, and the elements that clarified their understanding. Thus, difficulties, internal conflicts and other matters inherent in this research s object could be captured, as well as its integration with the community, support received, and linking with the federal level